The diet contribution and habitat selection of the common periwinkle Littorina littorea depending on infection with parasites and seasonality - Gronwald, Friederike; Bommarito, Claudia; Díaz-Morales, Dakeishla M; Manfrin, Alessandro; Martinez Reyes, Cindy; Nachev, Milen; Sures, Bernd; Weinberger, Florian (PANGAEA, 2025)
The common periwinkle Littorina littorea is an ecologically important grazer and serves as the first intermediate host for several trematode species in the Baltic Sea, especially for the fluke Cryptocotyle lingua. In this series of experiments and analyses, we tested whether the food sources contributing to the diet and the habitat selection differ depending on the infection status of the periwinkle and the season. (1) A spatial pattern analysis was conducted to investigate the habitat composition and availability of food sources at the study site Möltenort, Kiel Bight (54.37°N, 10.19°E), (2) the habitat choice of the periwinkle was observed in-situ by a mark and recapture experiment, and (3) the composition of the diet of L. littorea (based on stable isotope composition of carbon and nitrogen isotopes) was analysed. All experiments were conducted in spring, summer and autumn.
Keywords: Baltic Sea; Littorina littorea; parasite-host-system; Seasonality; stabe isotopes